Approaching 65 Years: Is It Time to Consider Retirement of Vancomycin for Treating Methicillin-Resistant Staphylococcus aureus Endovascular Infections?. (9th April 2022) - Rose, Warren; Volk, Cecilia; Dilworth, Thomas J; Sakoulas, George
Abstract: Vancomycin was introduced nearly 65 years ago and remains the standard antibiotic for serious methicillin-resistant Staphylococcus aureus (MRSA) infections. Staphylococcus aureus remains highly susceptibility to vancomycin (>97%). Despite this, MRSA treatment failure with vancomycin is high in complicated bacteremia. Additionally, vancomycin can cause nephrotoxicity, leading to new therapeutic drug monitoring guidance. This demonstrates how difficult it is to dose vancomycin in a way that is both efficacious and safe, especially during long courses of therapy. Often underappreciated are the cost, resources, and complexity of vancomycin care at a time when alternative antibiotics are becoming cost comparable. This perspective highlights a bigger picture of how the treatment repertoires of many other diseases have changed and advanced since vancomycin's introduction in the 1950s, yet the vancomycin MRSA treatment standard remains. While vancomycin can still have a role, 65 years may be a practical retirement age for vancomycin in highly complex endovascular infections. Abstract : Vancomycin is the standard antibiotic for serious methicillin-resistant Staphylococcus aureus (MRSA) infections. This perspective highlights how treatment repertoires of many other diseases have changed and advanced since vancomycin's introduction in the 1950s, yet vancomycin, despite its complexity, remains the MRSA treatment standard.